2019
DOI: 10.1029/2019jd030298
|View full text |Cite
|
Sign up to set email alerts
|

PMC Turbo: Studying Gravity Wave and Instability Dynamics in the Summer Mesosphere Using Polar Mesospheric Cloud Imaging and Profiling From a Stratospheric Balloon

Abstract: The Polar Mesospheric Cloud Turbulence (PMC Turbo) experiment was designed to observe and quantify the dynamics of small‐scale gravity waves (GWs) and instabilities leading to turbulence in the upper mesosphere during polar summer using instruments aboard a stratospheric balloon. The PMC Turbo scientific payload comprised seven high‐resolution cameras and a Rayleigh lidar. Overlapping wide and narrow camera field of views from the balloon altitude of ~38 km enabled resolution of features extending from ~20 m t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
57
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(61 citation statements)
references
References 93 publications
2
57
0
Order By: Relevance
“…Finally, and similar to previous studies (Fuller-Rowell et al, 2010, 2016, we attribute the day-to-day variability of the semidiurnal tidal amplitudes and phases to changes of the zonal winds in the middle atmosphere altering the vertical propagation conditions. Although atmospheric tides are global-scale waves, their vertical propagation depends on the regional meteorological situation.…”
Section: Navgem-ha and Mr Winds And Tidal Day-to-day Variability And supporting
confidence: 84%
See 1 more Smart Citation
“…Finally, and similar to previous studies (Fuller-Rowell et al, 2010, 2016, we attribute the day-to-day variability of the semidiurnal tidal amplitudes and phases to changes of the zonal winds in the middle atmosphere altering the vertical propagation conditions. Although atmospheric tides are global-scale waves, their vertical propagation depends on the regional meteorological situation.…”
Section: Navgem-ha and Mr Winds And Tidal Day-to-day Variability And supporting
confidence: 84%
“…We optimized these vertical wavelength values considering the results of previous studies using meteor radars investigating the vertical wavelengths of tides (Yu et al, 2013;Davis et al, 2013;Fritts et al, 2019). These earlier studies showed that the vertical wavelengths for most of the tidal modes are much larger than 25 km.…”
Section: Local and Global Diagnosticsmentioning
confidence: 99%
“…For example, in the case of airglow imagers, the vertical dimension is not. To overcome the relative large thickness of the airglow layer of a few kilometers, high‐resolution ground‐ and balloon‐based images of noctilucent clouds (NLCs) have been recently shown to be useful to study KHI with high spatial and temporal resolution (e.g., Baumgarten & Fritts, ; Fritts et al, , ).…”
Section: Introductionmentioning
confidence: 99%
“…The mean winds are regularized using a 10 km vertical retrieval kernel, the diurnal and semidiurnal tides are retrieved applying a 16 km vertical retrieval kernel. We optimized these vertical wavelength values considering the results of previous studies using meteor radars investigating the vertical wavelengths of tides (Yu et al, 2013;Davis et al, 2013;Fritts et al, 2019). These earlier studies showed that the vertical wavelengths for most of the tidal modes are much larger than >25 km.…”
mentioning
confidence: 99%